Financing innovative economic development in Sub-Saharan Africa: the role of mobile payment systems - T. F. Alhassan; A. J. Kouadio (Управление)
Electronic payments like mobile banking services have been associated with unprecedented access to financial services in economies, where a large section of the population was underfunded or underfunded due either due to lack of proximity to bank branches. However, the continuous development of electronic payment systems, especially mobile payment in sub-Saharan Africa has brought about a rise in volume of cashless transactions, thereby reducing the use of cash for payment. This therefore promotes financial integration among the segments of the population as it offers those without access to the formal banking system a safe and efficient payment alternative to cash. Also, electronic payment usage also has enormous benefits to governments as it will potentially help collect more tax revenue by providing a clear electronic trail and transparent transactions that can readily be taxed.Our study considers how mobile money services influence innovative economic growth. A linear regression analysis sub-Saharan African data for period 2011-2018 has been carried out. It has been revealed that mobile services and payments system have significant positive effect on economic growth, hence innovative development of the region. Based on these findings it is concluded that mobile payment services or systems are critical aspect of financial intermediation in sub-Saharan Africa as they offer them funds that can be drawn into the formal financial system from resources from both the population with bank accounts and the population without bank accounts, which can contribute to innovative economic growth in the region.